Impact of CYP3A5 genotype on tacrolimus versus midazolam clearance in renal transplant recipients: new insights in CYP3A5-mediated drug metabolism. (September 2013) - de Jonge, Hylke; de Loor, Henriette; Verbeke, Krisitin; Vanrenterghem, Yves; Kuypers, Dirk RJ
Background & aim: In vitro studies have identified both midazolam and tacrolimus as dual CYP3A4 and CYP3A5 substrates. In vivo ; however, the CYP3A5 genotype has a marked impact on tacrolimus pharmacokinetics, whereas it seems not to affect midazolam pharmacokinetics. The aim of the current study was to explore this paradigm in a relevant clinical setting.Patients & methods: A case–control study in 80 tacrolimus-treated renal transplant recipients comparing systemic and apparent oral midazolam clearance and tacrolimus pharmacokinetics in CYP3A5 expressers ( CYP3A5*1 allele carriers) and CYP3A5 nonexpressers ( CYP3A5*3/*3 ) was performed.Results: CYP3A5 expressers display an approximately 2.4-fold higher tacrolimus clearance as compared with CYP3A5 nonexpressers, whereas there are no differences in systemic and apparent oral midazolam clearance.Conclusion: These data confirm that in vivo CYP3A5 plays an important role in tacrolimus metabolism, while its contribution to midazolam metabolism in a relevant study population is limited. Furthermore, these data suggest that midazolam is to be considered as a phenotypic probe for in vivo CYP3A4 activity rather than combined CYP3A4 and CYP3A5 activity. Original submitted 12 March 2013; Revision submitted 10 July 2013